已知数列{an}的前n项和Sn=1-kan(k>0,n∈N*).
(1)用n、k表示an;
(2)数列{bn}对n∈N*均有(bn+1-bn+2)lga1+(bn+2-bn)lga3+(bn-bn+1)lga5=0,求证:数列{bn}为等差数列;
(3)在(1)、(2)中,设k=1,bn=n+1,xn=a1b1+a2b2+a3b3+…+anbn,求证:xn<3.
(1)∵Sn=1-kan,
∴S1=a1=1-ka1,
∴a1=
∴an+1=Sn+1-Sn=(1-kan+1)-(1-kan),
∴an+1=kan-kan+1,即 (k+1)an+1=kan,
∵kk≠1解得an+1=an(1)
∵k>0,a1≠0,由(1)式易知an≠0,n≥1,
∴=
故该数列是公比为,首项为的等比数列,
∴an=×()n-1.
证明:(2)∵(bn+1-bn+2)lga1+(bn+2-bn)lga3+(bn-bn+1)lga5=0,
∴(bn+1-bn+2)lg+(bn+2-bn)lg[(×()2]+(bn-bn+1)lg[(×()4]=0…①
令lg=m,lg=n,则m,n均不为0
则①式可化为m(bn+1-bn+2)+(m+2n)(bn+2-bn)+(m+4n)(bn-bn+1)=0
即bn+2+bn=2bn+1,
即数列{bn}为等差数列;
(3)若k=1,an=×()n-1=()n,
又∵bn=n+1,
∴xn=×2+()2×3+()3×4+…+()n(n+1)…①,
∴xn=()2×2+()3×3+…+()nn+()n+1(n+1)…②
①-②得xn=1+[()2+()3+…+()n]-()n+1(n+1)=-()n
∴xn=3-(n+3)()n
∵(n+3)()n>0
∴xn<3